A College Buddy System with Matching Algorithm - Ko, Chi Ling (Journal of International Conference Proceedings, 2025)
This study introduces BuddyIN, a mobile application developed to strengthen peer mentorship and collaborative learning among students at INTI International College Penang. The primary objective is to provide an intelligent platform that efficiently matches students with suitable study partners while offering academic support features. The system was developed using the Waterfall methodology, encompassing requirement gathering, system design, implementation, testing, deployment, and maintenance. Key components include the buddy matching algorithm, AI chatbot integration, intuitive user interface design, and extensive system testing to ensure functionality and reliability. The matching algorithm effectively pairs senior students with freshmen based on user-input data, fostering meaningful academic connections. The project successfully produced a fully functional mobile application that promotes productive study partnerships, delivers real-time academic assistance, and enhances students’ learning experiences, time management, and overall academic performance.